Industrial residues as substrate components for the production of Ilex paraguariensis seedlings - Gabira, Monica Moreno; Gomes, João Felipe Penteado; Kratz, Dagma; Wendling, Ivar; Stuepp, Carlos André (Comunicata Scientiae, 2020)
Ilex paraguariensis is an important forest species in Brazil. Recently, the development of new products has increased seedlings demand and consequently, the interest in new products to use as substrates like residues from industries. We aimed to evaluate the viability of using industrial residues as substrates to produce yerba mate seedlings. We formulated thirteen substrates with coconut fiber, carbonized and decomposed yerba mate industrial residues in different ratios, which were compared to two commercial substrates, in a completely randomized design. The stratified seeds were placed in 110 cm³ tubes filled with the substrates. Plants were kept in a greenhouse for 135 days, shade house (70%) for 30 days, and rustification area in full sunlight for 15 days, under fertigation after 30 days of sowing. We evaluated montlhy the survival, height, and stem diameter, and at the end of the production period, we evaluated shoot and root dry mass. From the data obtained, we calculated the total dry mass and ‘Dickson quality index’. The substrates formulated with coconut fiber and decomposed yerba mate industrial residue can be used to produce yerba mate seedlings, but it depends on the ratio of the substrate components. Substrates with higher total porosity and microporosity provided seedlings with biometric characteristics similar to those produced in commercial substrates. The carbonized yerba mate residue reduced seedling growth when used in a percentage equal to or higher than 50% in the substrate.